Food and medical aid for flood-affected communities in Aceh Tamiang - Legito Legito; Nurul Afni; Fricles Ariwisanto Sianturi; Arjon Samuel Sitio; Muhammad Dicky Syahputra Lubis (International Journal of Community Service Implementation, 2026)
The emergency response period following a flash flood holds a strategic role in ensuring the survival of survivors and preventing the decline of public health status. This community service program aims to assist flood victims in Aceh Tamiang Regency by providing immediate logistics in the form of ready-to-eat food and basic medical packages to meet urgent nutritional and health needs. The activity was conducted on December 16 and 22, 2025, using a rapid response approach centered at evacuation points. The method used was participatory distribution with priority given to vulnerable groups. Results show that the program succeeded in distributing nutritional support that met the immediate energy requirements of survivors and effectively improved access to essential medicines. The program also fostered social support among the displaced population through active coordination with local health posts. As a significant contribution, this activity establishes an integrated emergency logistics distribution model that combines nutritional fulfillment and basic medical intervention to minimize post-disaster morbidity risks in isolated areas.